Changes in the modulation of spinal pain processing are related to severity in irritable bowel syndrome. Issue 7 (2nd April 2013) - Bouhassira, D.; Moisset, X.; Jouet, P.; Duboc, H.; Coffin, B.; Sabate, J.‐M.
Abstract Background In irritable bowel syndrome (IBS) patients can be divided in two groups according to inhibition or facilitation of the RIII nociceptive spinal reflex induced by rectal distension. We further investigated the differences in pain processes in these two groups and their relationship to clinical symptoms. Methods This study included 10 female IBS‐C patients with facilitation (Group F) and 10 patients with inhibition (Group I) of the RIII reflex recorded on the left lower limb during slow‐ramp rectal distension, and 11 healthy female volunteers. Diffuse noxious inhibitory control (DNIC)‐induced inhibition was assessed by measuring the effects of noxious cold stimulation of the right hand on the RIII reflex and the concomitant sensation of pain. Functional magnetic resonance imaging (fMRI) was performed to compare the changes in brain activity induced by painful and non painful rectal distension. Irritable bowel syndrome symptom severity, mood, anxiety, and catastrophizing were also systematically assessed. Key Results Unlike the patients of Group I and healthy volunteers, Group F patients displayed no inhibition of the RIII reflex or of concomitant pain sensation during immersion of the hand in ice‐cold water. The reduction of the inhibition induced by heterotopic noxious stimuli was directly correlated with the severity of IBS symptoms, but not with psychological symptoms. The fMRI study showed that non‐painful and painful rectal distension induced similar changes in brain activity in the two groups of patients. Conclusion & Inferences Alterations of the modulation of spinal pain processing in IBS correlates with symptom severity but not with psychological factors or brain activity.